DIABETIC CONTROL IN ELDERLY AND COGNITIVE DECLINE - Nur Riviati; Ridzqie Dibyantari; Rini Nindela; Bintang A Prananjaya; Afifah Z Salsabila; Aidi A Putri (Fakultas Kedokteran Universitas Sriwijaya, 2021)
As the population aging increasing rapidly worldwide, including in Indonesia, the health problems come as consequences as well as delivering health and social care. At this moment 14% of Indonesian consist of aging population, defined as those above 60-year-old of age. Aging ameliorates normal hormonal and immunology system, consequently elderly are prone to infection as well as metabolic disorder, namely diabetes. Good glycemic control in elderly can prevent cognitive decline such as mild cognitive impairment and dementia. The aim of this paper is to discuss the importance of diabetic control in elderly, focusing on cognitive decline related to diabetes